Pengaruh Pendapatan dan Kesehatan dan Keselamatan Kerja (K3) terhadap Kesejahteraan Buruh di Pelabuhan Sintete Perspektif Maqasid Syariah - Ana, Putri; Sukmawati, U. Sulia; Maskupah, Maskupah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
include income level, health level, education, lifestyle and so on. This research aims to analyze the influence of income and occupational health and safety (K3) on the welfare of workers at Sintete Port from a maqasid sharia perspective, both partially and simultaneously. This research method uses a quantitative approach with the type of field research. The data used is primary data obtained from distributing questionnaires to 28 pioneer ship workers at Sintete Port and the profile of Sintete Port. The primary data obtained was then tested using multiple linear regression. The results of this research show that partially income and occupational health and safety (K3) have a positive effect on the welfare of workers at Sintete Port from a maqasid sharia perspective. Income with a coefficient value of 0.891 and a calculated t value > t table (5.591 > 1.708). Meanwhile, occupational health and safety (K3) has a coefficient value of 0.400 and a calculated t value > t table (4.950 > 1.708). Simultaneously, income and occupational health and safety (K3) have a positive effect on the welfare of workers at Sintete Port from a maqasid sharia perspective with a calculated F value > F table (28.132 > 3.37).